2022
DOI: 10.1177/11772719221081789
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Prognostic Biomarker Soluble Urokinase Plasminogen Activator Receptor in the Emergency Department: A Tool for Safe and More Efficient Decision-making

Abstract: Introduction: Risk stratification in the emergency departments (EDs) is in critical need for new applications due to ED overcrowding and hospitalization of older people. We aimed to evaluate the expediency, efficiency and safety of a prognostic biomarker, soluble urokinase plasminogen activator receptor (suPAR), as a tool for the risk assessment of patients arriving at the ED. Methods: We performed a comparative cross-sectional study in 2 emergency departments (EDs), suPAR measurements being incorporated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Data on discharge within 24 hours from the hospital were reported by 5 observational studies. [ 19 , 21 , 23 , 31 , 32 ] This revealed a positive correlation between patients with high suPAR levels and discharge from the hospital within 24 hours (RR = 0.42; 95% CI = 0.32–0.56; P < .00001; I 2 = 80%) as shown in Supplementary Figure S4, http://links.lww.com/MD/K600 . Sensitivity analysis was carried out by removing 1 study, [ 19 ] this resulted in a very slight alteration in the risk (RR = 0.46; 95% CI = 0.40–0.53; P < .00001) and revealed mild heterogeneity (I 2 = 41%; P = .17) (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Data on discharge within 24 hours from the hospital were reported by 5 observational studies. [ 19 , 21 , 23 , 31 , 32 ] This revealed a positive correlation between patients with high suPAR levels and discharge from the hospital within 24 hours (RR = 0.42; 95% CI = 0.32–0.56; P < .00001; I 2 = 80%) as shown in Supplementary Figure S4, http://links.lww.com/MD/K600 . Sensitivity analysis was carried out by removing 1 study, [ 19 ] this resulted in a very slight alteration in the risk (RR = 0.46; 95% CI = 0.40–0.53; P < .00001) and revealed mild heterogeneity (I 2 = 41%; P = .17) (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…The pooled analysis revealed a significant association between patients with high suPAR levels and length of hospital stay as compared to patients with low suPAR levels. It showed that patients with high suPAR levels stayed for a greater duration in the hospital as compared to patients with low suPAR levels (WMD = 2.82 days; 95% CI = 1.46-4.19; P < .0001; I 2 = 100%) as shown [21] Prospective Cohort Two Finnish hospital regions (Helsinki and Mikkeli) -High = >6 Low = <3 Holstein et al 2022 [32] Comparative Holstein et al 2022 [32] 330 in Supplementary Figure S5, http://links.lww.com/MD/K601. The exclusion of 1 study [21] was done to perform sensitivity analysis, however, it did not lead to a significant change in the heterogeneity of the included studies (Fig.…”
Section: Length Of Hospital Staymentioning
confidence: 93%
See 2 more Smart Citations
“…In a clinical setting where diagnostic accuracy is crucial, the search for additional and complementary biomarkers to troponin reflects the growing need to improve the sensitivity and specificity of diagnoses. 5,6 cTN Cardiac troponin is one of the main biomarkers used in the assessment of cardiac damage. Its complex consists of the subunits troponin I (TnI), troponin T (TnT), and troponin C (TnC).…”
Section: Introductionmentioning
confidence: 99%